Analisis Faktor-Faktor Yang Memengaruhi Capaian Realisasi Penerimaan Negara Bukan Pajak Pada Bandar Udara Karel Sadsuitubun Langgur - Sucik Puji Utami; St. Siaila; Joko Rizkie Widokarti (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The purpose of this research was to analyze the effect of PNBP targets, PNBP deposits and the number of aircraft movements on the realization of PNBP at Karel Sadsuitubun Langgur Airport. The hypothesis in this research was tested by multiple linear regression analysis using the t test with a significance level of 0.05. The population in this research were all financial reports that included PNBP targets, realized PNBP deposits and all air transport traffic reports containing the number of aircraft movements at Karel Sadsuitubun Langgur Airport. The samples used are financial reports covering PNBP targets, realization of PNBP deposits and air transport traffic reports containing the number of aircraft movements at Karel Sadsuitubun Langgur Airport for 36 months from January 2017 to December 2019. Partial test results (test t) shows that the tcount for the PNBP target variable is -173.347 with a significance of 0.000; tcount for PNBP payment variable of 418,725 with a significance of 0,000; tcount for the variable number of aircraft movements is -1.028 with a significance of 0.05. Thus, hypothesis one is rejected where the PNBP target variable (X1) partially has a negative effect on the realization of PNBP achievement (Y) at Karel Sadsuitubun Langgur Airport, the second hypothesis is accepted where the PNBP payment variable (X2) partially has a positive effect on the realization of PNBP achievement ( Y) at Karel Sadsuitubun Langgur Airport, and the third hypothesis is rejected because the variable number of aircraft movements (X3) has no effect on the realization of PNBP (Y) achievements at Karel Sadsuitubun Langgur Airport.